Evaluation of temperature on survival, metabolism, and morphological changes in Palm ruff (Seriolella violacea) larvae - Begoña Cárcamo; Boris Dewitte; Alexandra Parouffe; Aurélien Paulmier; Véronique Garçon; Laura Ramajo; Sebastián San Martín; Juan Varas; Marcia Oliva; Edison Serrano; Nieves Sandoval; Katherine Jeno; et al. (Aquaculture, 2026)

Evaluating future climate change exposure of marine habitat in the South East Pacific based on metabolic constraints - Alexandra Parouffe; Véronique Garçon; Boris Dewitte; Aurélien Paulmier; Ivonne Montes; Carolina Parada; Ariadna Mecho; David Veliz (Frontiers in Marine Science, 2023)
Introduction On-going climate change is now recognized to yield physiological stresses on marine species, with potentially detrimental effects on ecosystems. Here, we evaluate the prospect of using climate velocities (CV) of the metabolic index (Φ) for assessing changes in habitat in the South East Pacific. Methods Our approach is based on a species with mean ecophysiotype (i.e. model species) and the use of a global Earth System Model simulation (CESM-LE) under RCP 8.5 scenario. The SEP is chosen as a case study as it hosts an Oxygen Minimum Zone and seamounts systems sustaining local communities through artisanal fisheries. Results and Discussion Our results indicate that CV Φ pattern is mainly constrained by the oxygen distribution and that its sign is affected by contrasting oxygen trends (including a re-oxygenation in the upper OMZ) and warming. We further show that CV Φ is weakly dependent on physiological traits composing Φ, which conveys to this metrics some value for inferring the projected mean displacement and potential changes in viability of metabolic habitat in a region where physiological data are scarce. Based on sensitivity experiments to physiological traits and natural variability, we propose a general method for inferring broad areas of climate change exposure regardless of species-specific Φ. We show in particular that for the model used here, the upper OMZ region can be considered a “safe” area for the species with ecophysiotype close to that of 71 species used to derive the model species. Limitations of the approach and perspectives of this work are also discussed.